Rehabilitasi Sarana Pendidikan dalam Meningkatkan Kualitas Pembelajaran di Madrasah Tsanawiyah Ziyadatut Taqwa - Linda Khilyana; Yanti Wulandari; Imamul Muttakin (Action Research Journal, 2025)
This study aims to determine the process of rehabilitation of educational facilities in improving the quality of learning at MTs Ziyadatut Taqwa. The research method used is a qualitative research method with a descriptive approach carried out through field research. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that rehabilitation of educational facilities has a significant positive impact on the quality of learning. With good and well-maintained educational facilities, students can learn safely and comfortably, concentrate, and increase student motivation and interest in learning. Rehabilitation of educational facilities plays an important role in improving the quality of learning at MTs Ziyadatut Taqwa by involving planning consultants to conduct damage identification mapping, prepare rehabilitation plans, and manage budgets effectively. It can be concluded that rehabilitation of facilities requires a comprehensive strategy in improving the quality of learning, facilitating a more effective education process, and providing a positive learning experience for students and educators